The ghost in the machine: disembodiment in schizophrenia - two case studies - Haan, Sanneke de; Fuchs, Thomas (Psychopathology, 2010)
The notion of embodiment is central to the phenomenological approach to schizophrenia. This paper argues that fundamental concepts for the understanding of schizophrenia have a bodily dimension. We present 2 single cases of first-onset schizophrenic patients and analyze the reports of their experiences. Problems such as loss of self, loss of common sense, and intentionality disorders reveal a disconnectedness that can be traced back to a detachment from the lived body. Hyperreflectivity and hyperautomaticity are used as coping mechanisms, but reflect the same problem of the split between body and mind. It is argued that the sole focus on cognitive impairments leads to a distorted image of schizophrenia, and that the acknowledgment of its fundamental bodily roots enables one to see the coherence between the diverse symptoms. As for the practical implications of the phenomenological approach, further research is needed to investigate if and how body- and movement-oriented therapies might strengthen the embodiment of schizophrenic patients.